2022
DOI: 10.3389/fonc.2022.889144
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Lymph Node Dissection in Patients With Node-Positive Upper Urinary Tract Urothelial Cancer: A Retrospective Cohort Study

Abstract: PurposeThe value of lymphadenectomy during radical nephroureterectomy (RNU) remains unclear. This study aimed to determine the effects of the removed lymph node (RLN) counts, positive lymph node (pLN) counts, and pLN density (pLND) on survival outcomes in patients with node-positive upper urinary tract urothelial cancer (UTUC).MethodsA total of 306 patients with node-positive UTUC in the Surveillance, Epidemiology, and End Results database between 2004 and 2016 were identified. Multivariable Cox regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Meanwhile, positive lymph node density (best cutoff = 27%) was associated with lower OS and CSS (HR: 1.62, p = 0.036, and HR: 1.75, p = 0.014, respectively). The 5-year OS rate for patients with density < 27% was 18.7%, compared to 34.2% for those with density ≥ 27% (p < 0.05) [100].…”
Section: Lymph Node Statusmentioning
confidence: 83%
“…Meanwhile, positive lymph node density (best cutoff = 27%) was associated with lower OS and CSS (HR: 1.62, p = 0.036, and HR: 1.75, p = 0.014, respectively). The 5-year OS rate for patients with density < 27% was 18.7%, compared to 34.2% for those with density ≥ 27% (p < 0.05) [100].…”
Section: Lymph Node Statusmentioning
confidence: 83%
“…Xia et al demonstrated that in patients with node-positive UTUC, removing more LNs does not offer a better therapeutic effect. However, positive LN density provided additional prognostic value for CSS and OS [ 21 ]. Another study showed that in clinically node-positive patients with UTUC, performing LND in addition to RNU at any clinical stage does not seem to have a significant impact on OS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%